2022
DOI: 10.1108/jstpm-08-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

A review of telehealth during the COVID-19 emergency situation in the public health sector: challenges and opportunities

Abstract: Purpose The purpose of this study is to provide current state of knowledge on how the COVID-19 emergency situation necessitated the behaviour influencing use and acceptance of telehealth. This study interlinks the health belief model (HBM) and the unified theory of acceptance and use of technology (UTAUT) to highlight the challenges and opportunities as a result of the COVID-19 pandemic in the public health sector. Design/methodology/approach This study used three online databases (Emerald publishing, Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…All the participants cited the importance of the human factor in healthcare system, and they see telehealth as a threat to this. 47 The power of voice emerged as very important. 47 Associated with this concern is the issue that GPs have less and less time for patients as they spend more time on technology and/or documentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the participants cited the importance of the human factor in healthcare system, and they see telehealth as a threat to this. 47 The power of voice emerged as very important. 47 Associated with this concern is the issue that GPs have less and less time for patients as they spend more time on technology and/or documentation.…”
Section: Discussionmentioning
confidence: 99%
“… 47 The power of voice emerged as very important. 47 Associated with this concern is the issue that GPs have less and less time for patients as they spend more time on technology and/or documentation. The key informants raised concerns over the mental well-being of healthcare workers, with some reporting having seen their own GPs affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to findings reported by Ng and Park ( 2021 ), 81.2% of survey respondents reported that their medical providers offered telehealth services during the pandemic. Another study suggested that telehealth was rapidly used by doctors and patients to reduce COVID-19 transmission (Maleka & Matli, 2022 ). Telehealth also offered significant help to those with chronic diseases that required seeing a doctor regularly to understand and manage their conditions (Bitar & Alismail, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a study that involves both perceived quality and perceived risk would be interesting to get comprehensive insight. The Unified Theory of Acceptance and Use of Technology (UTAUT) has commonly been used for research regarding technology adoption in health-related industries regarding several aspects, such as cost and interaction aspects (Maleka & Matli, 2022), situational challenges and health concerns (Barua & Barua, 2021), customer attitude and condition (Donmez-Turan, 2020). However, those studies were not done explicitly for m-health users and were only conducted in Bangladesh and Turkey.…”
Section: Introductionmentioning
confidence: 99%